2012
DOI: 10.2217/npy.12.39
|View full text |Cite
|
Sign up to set email alerts
|

Substance-use disorders in adolescents and adults with ADHD: focus on treatment

Abstract: SUMMARY A high prevalence of comorbidity of ADHD and substance-use disorders (SUDs) has been shown in the literature. In this article, the literature for the treatment of adolescents and adults with co-occurring ADHD and SUD is examined. Findings from pharmacotherapy suggest mild improvement in ADHD without demonstrable changes in SUD unless the addiction was stabilized prior to treating the ADHD. No unique adverse effects, worsening of SUD, misuse or diversion of stimulants are reported in the included studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 69 publications
1
20
0
1
Order By: Relevance
“…This is important because ADHD symptoms can interfere with SUD treatment and/or SUD can complicate the treatment of ADHD. It is advisable to first start SUD treatment, followed by ADHD treatment as soon as possible thereafter [27]. When the SUD is too severe, brief residential treatment may be appro priate.…”
Section: Consensus Statement For the Treatment Of Adhd And Sudmentioning
confidence: 99%
See 2 more Smart Citations
“…This is important because ADHD symptoms can interfere with SUD treatment and/or SUD can complicate the treatment of ADHD. It is advisable to first start SUD treatment, followed by ADHD treatment as soon as possible thereafter [27]. When the SUD is too severe, brief residential treatment may be appro priate.…”
Section: Consensus Statement For the Treatment Of Adhd And Sudmentioning
confidence: 99%
“…On the other hand, medication has more positive effects when combined with psychotherapy, while ADHD pharmaco-therapy by itself is generally not effective in reducing the use of substances and is associated with a higher frequency of adverse effects and treatment discontinuation [7, 27]. …”
Section: Consensus Statement For the Treatment Of Adhd And Sudmentioning
confidence: 99%
See 1 more Smart Citation
“…The following demographic/methodologic factors did not significantly moderate the associations between childhood ADHD and substance outcomes: gender, age, race, publication year, sample source, version of the Diagnostic and Statistical Manual of Mental Disorders used to diagnose ADHD, family history of SUD, cognitive impairment, executive dysfunction, and family environment. 16 Lee et ADHD is associated with an earlier age at onset of substance use and a higher likelihood of use of a variety of substances. [17][18][19] Brook et al 20 reported that the diagnosis of ADHD poses an increased risk of SUD into adulthood; meeting criteria for a diagnosis of ADHD in adolescence is associated with developing SUDs in a subject' s 20s and 30s.…”
Section: Epidemiology Of Suds Among Individuals With Adhdmentioning
confidence: 99%
“…The published RCTs of MPH for ADHD in adult SUD populations in outpatient settings (Levin et al, 2007, Levin et al, 2006a, Schubiner et al, 2002 have all provided additional CBT treatment along with the medication. CBT in adults with ADHD has shown to be effective with moderate effect size (Safren et al 2006) therefore, it has been suggested that the improvement as a result of psychosocial treatment would mask the medication effect (Riggs et al, 2011, Thurstone et al, 2010, Wilens and Morrison, 2012. CBT trials in adults with ADHD have included participants on medication (Safren et al, 2005, Solanto et al, 2010.…”
Section: Pharmacotherapymentioning
confidence: 99%